Digital Literacy among Women Entrepreneurs in Rural Areas / Roseliza Hamid...[et al.] - Hamid, Roseliza; Ahmad Zukarnain, Zuriani; Nik Md Salleh, Nik Sarina; Nik Ismail, Nik Nor Hasimah (Universiti Teknologi MARA Cawangan Kelantan, 2020)
The ability to use information and communication technologies has become crucial nowadays specifically to businesses. Hence, this paper makes an attempt to report the findings on women entrepreneurship and digital literacy skills. It focuses on digital knowledge and its usage by respondents who were participants of Program Inkubator Usahawan Komuniti (PIUK) Jeli organized by Pusat Pembangunan Komuniti dan Usahawan (PPKU), UiTM Kelantan Branch. All participants were selected among women entrepreneurs from rural areas who are mostly home-based micro traders. They are also members of Amanah Ikhtiar Malaysia (AIM) Jeli branch. The questionnaires were distributed among participants in order to collect data which were later analyzed and described through descriptive analysis. The findings showed that most of the respondents have knowledge of the Internet, are moderate in digital literacy skills, and have been using the Internet via smart phones and tablets to browse Facebook and WhatsApp. Thus, this study suggests more digital programs need to be conducted to enhance skills among women entrepreneurs in utilizing the Internet for businesses